What helps hospital staff in times of crisis: qualitative results of a survey on psychosocial resources and stressors in German hospitals during the COVID-19 pandemic - Schmidt-Stiedenroth, Kira; Guthardt, Lisa; Genrich, Melanie; Köhne, Mara; Stiawa, Maja; Erschens, Rebecca; Junne, Florian; Maatouk, Imad; , The SEEGEN-Consortium; Gündel, Harald; Angerer, Peter; Müller, Andreas (Frontiers in Public Health, 2023)
Background Even before the COVID-19 pandemic, hospital workers faced a tremendous workload. The pandemic led to different and additional strain that negatively affected the well-being of employees. This study aims to explore psychosocial resources and strategies that were used by hospital staff. Methods In the context of an intervention study, employees of three German hospitals were questioned in writing in summer and fall 2020. Five open-ended questions about the pandemic were asked to capture corresponding effects on daily work routine. Answers of 303 participants were evaluated using structuring qualitative content analysis. Results Significant stressors and resources were identified in the areas of work content and task, social relations at work, organization of work, work environment and individual aspects. Stressors included, for example, emotional demands, conflicts, an increased workload, time and performance pressure. Important resources mentioned were, among others, the exchange with colleagues and mutual support. Sound information exchange, clear processes and guidelines and a positive work atmosphere were also important. In addition, the private environment and a positive mindset were perceived as helpful. Conclusion This study contributes to a differentiated understanding of existing psychosocial resources of hospital staff in times of crisis. Identifying and strengthening these resources could reduce stress and improve well-being, making hospital staff better prepared for both normal operations and further crisis situations.